Pengaruh Teknik Relaksasi Autogenik terhadap Intensitas Kecemasan dan Nyeri pada Pasien Post Operasi di Ruang Perawatan Umum - Meita Prima Dewi; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (Jurnal Siti Rufaidah, 2026)
Anxiety and pain are common problems experienced by postoperative patients and may negatively affect physiological and psyhological conditions as well as the recovery process. Management of anxiety and pain can be carried out throught pharmacological and non-pharmacological approaches, one of which is the autogenic relaxation technique. This technique is safe, simple easy to learn and does not cause side effects so it can be applied by healthcare professionals and performed independently by patients. This study aimed to determine the effect of autogenic relaxation on anxiety levels and pain intensity in postoperative patients in the general ward. This study employed a pre-experimental design with a pretest-posttest without control approach. The sample consisted of 31 respondents selected using a purposive sampling technique. Data were collected using the Hamilton Rating Scale for Anxiety (HRS-A) to measure anxiety levels and the Numeric Rating Scale (NRS) to assess pain intensity. The result of the Paired Sample T-test showed a p-value of 0,0001 (< 0,05), indicating a significant decrease in the mean anxiety level from moderate to mild after the intevention. The wilcoxon test also showed a p-value of 0,0001 (< 0,05), demonstrating a significant difference in pain intensity before and after the intervention, from moderate pain to mild pain. It can be cocluded that the autogenic relaxation technique has a significant effect on reducing anxiety levels and pain intensity in postoperative patients. This technique is recommended as a non-pharmacological intervention that can be applied by healthcare professionals to enhance patient comfort and support the postoperative recovery process.